Narrative gravity. conversation, cognition, culture - Nair, Rukmini Bhaya (New Delhi: New York: Oxford University Press, 2002)
In this elegantly written and theoretically sophisticated work, Rukmini Bhaya Nair asks why human beings across the world are such compulsive and inventive storytellers. Extending current research in cognitive science and narratology, she argues that we seem to have a genetic drive to fabricate as a way of gaining the competitive advantages such fictions give us. She suggests that stories are a means of fusing causal and logical explanations of 'real' events with emotional recognition, so that the lessons taught to us as children, and then throughout our lives via stories, lay the cornerstones.
Includes bibliographical references (p. [399]-417) and index.
Keywords: Discourse analysis, Narrative; Discourse analysis -- Psychological aspects; REFERENCE